Primary Ovarian Pregnancy after Bilateral Tubal Sterilization - Lama, Poonam; Jha, Gautam; Amatya, Indra Prasad (Journal of Nepal Health Research Council, 2023)
Tubal sterilization is considered a permanent method of contraception because it is highly effective. However, pregnancy can still occur following a successful procedure and such pregnancies are likely to be ectopic. Primary ovarian pregnancy is one of the rarest forms of ectopic pregnancy having incidence of 1/7000-1/40,000 in live births and 0.5-3% of all ectopic gestations. In this paper, we report a rare case of ovarian pregnancy after tubal sterilization. All women who are offered this procedure should always be educated about its failure rate. And in women presenting with acute abdomen, a prior history of tubal sterilization doesn’t preclude the possibility of ectopic pregnancy. Keywords: Contraception; ovarian pregnancy; tubal sterilization